Ślubowanie duchowieństwa w województwie wrocławskim na wierność Polskiej Rzeczpospolitej Ludowej i Jej Rządowi w kwietniu 1953 r. oczami aparatu represji - Klementowski, Robert (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
The Decree of February 9, 1953 on appointments of clergy to church positions was a legal act crowning a broad array of actions aiming at subjugation of the Catholic Church to the communist authorities by forcing the clergy to make a pledge of allegiance to the state, and by gaining influence on filling church positions. This problem is presented through a reconstruction of the realization of the act of making the pledge – on the example of Lower Silesia and from the point of view of the political police.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne